PROFIL KREATIVITAS SISWA KELAS VIII SMP N 1 KALAWAT DALAM PENYELESAIAN MASALAH GEOMETRI DITINJAU DARI GAYA BELAJAR MATEMATIKA - Pulukadang, Rosiah J; Manurung, Ontang; Mokodompit, Dita Fatmawati (Universitas Negeri Manado, 2020)
ABSTRACT. This research was to described the profile of studentscreativity in solving geometry problems in terms of learning styles of visual, auditory and kinesthetic. This research was categorized as a descriptive research with a qualitative approach. This research was conducted at SMP Negeri 1 Kalawatin the odd semester of the 2019/2020 academic year. The subjects in this research were three eighth grade students who had visual, auditory and kinesthetic learning styles. Data collection techniques in this research used test and interview, while data analysis techniques used data reduction, data presentation, conclusion drawing and verification. The results of data analysis show that visual style subjects can meet fluency, flexibility and novelty indicators, auditory style subjects can meet fluency and novelty indicators but do not meet flexibility indicators, and kinesthetic-style subjects can meet fluency and novelty indicators but not indicators of flexibility. Thus it can be concluded that the students with visual, auditory and kenesthetic learning styles have different levels of creative thinking abilities.Â Key Words: Creativity, Learning Style, Geometry